Production, purification and characterization of alkaline protease by ascidian associated Bacillus subtilis GA CAS8 using agricultural wastes. Issue 2 (April 2015) - Sathishkumar, Ramamoorthy; Ananthan, Gnanakkan; Arun, Jeganathan
Abstract: In the present study, protease producing Bacillus subtilis GA CAS8 was isolated from marine ascidian Phallusia arabica and identified by 16 S rRNA gene sequence. Optimization of culture condition for protease production using agricultural wastes had done by response surface methodology. The statistical optimization studies revealed that the protease production was higher when the groundnut oil cake and cabbage leaf were used as substrate. The protease activity was optimum at 50 °C and pH 9 and it retained more than 60% of activity, even at pH 12 and the molecular weight of the purified protease was 41 kDa. The activity of the purified protease was stimulated by Mg 2+ and Ca 2+ and it was resistant to Tween 20, Tween 40 and SDS. The protease activity was strongly inhibited in the presence of EDTA. The remarkable properties such as temperature and pH stability found with this enzyme assure that it could be a potential candidate for industrial applications.